Réponses

2014-02-04T18:02:35+01:00
A) x = 3

c) x = - 2

d1) x = 90

d2) x = 40

e) x = 1,2 / (1/3) = 1,2 * 3 = 3,6

f) x = 2/3 + 3/4 = 8/12 + 9/12 = 17/12

g) x = 0

h) x = 3 / (-6/5) = 3 * (-5/6) = -15/6 = - 5/2

i) -x+3=4 : x = - 1

j) - 2x = 13 : x = - 6,5

k) x = -11/12 - 1/8 = - 22/24 - 3/24 = - 25/24

l) 3x = 5,4: x = 1,8

m)  6x/6 - 1x/6 - 3x/6 = 2,5 : 2x/6 = 2,5 : x/3 = 2,5 : x = 7,5

n) 2,7 = -3x: x = - 0,9

o) 6x / -4 = -1 / 2 : 12x = 4 : 3x = 1 : x = 1/3

p) 25 = -24 x : x = - 25/24